(untitled) (Campo Abierto. Revista de Educación y Psicología, 2024)
The current education law LOMLOE passed in 2020, considers that Education for Sustainable Development (ESD) should be introduced in teacher training. By means of a descriptive observational study through an exhaustive documentary analysis of the teaching plans of the degrees in Early Childhood Education, Primary Education and Social Education of the University of Extremadura to review ESD training and the presence of the Sustainable Development Goals (SDGs). A total of 125 subjects, 231 competences and 773 TFG lines were analysed. It was detected that there is no subject in any degree that is ESD or similar and that many subjects include competences related to development education but there is a lack of competences related to sustainability. The degree in Social Education is the one with the most subjects and TFG lines related to the SDGs and the degree in Early Childhood Education the one with the least. Keywords: Education for sustainable development; curricular research; teaching; University; teacher.